Relationship between sarcopenia/myosteatosis and frailty in hospitalized patients with cirrhosis: a sex-stratified analysis. (July 2021) - Feng, Hongjuan; Wang, Xiaoyu; Mao, Lihong; Yu, Zihan; Cui, Binxin; Lin, Lin; Hui, Yangyang; Zhao, Xingliang; Xu, Xin; Fan, Xiaofei; Wang, Bangmao; Yu, Qingxiang; et al.
Background: Previous studies have shown that sarcopenia appears to be a significant contributor to physical frailty among outpatients with cirrhosis. However, the evidence is scant regarding the relationship between sarcopenia and multi-dimensional frailty among inpatients. We aimed to investigate the potential contribution of sarcopenia to frailty in hospitalized patients with cirrhosis in a sex-dependent manner. Methods: This cohort enrolled consecutive cirrhotics. Muscle quantity and quality were assessed using the computed tomography-based skeletal muscle index (SMI) and intramuscular adipose tissue content, respectively. Frailty phenotype was clarified by a self-reported Frailty Index. Multiple linear regression determined the association between sarcopenia and frailty phenotype. Results: A total of 202 cirrhotic patients with 48.5% male were included. The median Frailty Index was 0.13, rendering 17.3% subjects as frail. Among the 16 frail men, 68.8% had sarcopenia and 62.5% exhibited myosteatosis. In contrast, among the 19 frail women, 26.3% had sarcopenia and 15.8% exhibited myosteatosis. Frail patients had a significantly lower median SMI (42.80 cm 2 /m 2 ) compared with those with pre-frailty (48.23 cm 2 /m 2 ) and with robust status (50.82 cm 2 /m 2 ) in the male but not the female group. In male patients, multivariate linear regression implicated age (β  =  0.330, p  < 0.001), SMI (β  =  −0.260, p  < 0.001), albumin (β  =  −0.245, p  = 0.005), and sodium (β  =  −0.179, p  = 0.037) as independent risk factors for frailty. Conclusion: Sarcopenia is associated with multi-dimensional frailty in male patients with cirrhosis. It is tempting to incorporate sex-specific intervention with the purpose of mitigating frailty among inpatients.